Métodos de participação e Tecnologias de Informação e Comunicação: transformando participação em eParticipação - Slaviero, Cleyton; Garcia, Ana Cristina Bicharra; Maciel, Cristiano (Anais do Latin American Symposium on Digital Government (LASDiGov); 2012: Anais do IV Workshop de Computação Aplicada em Governo Eletrônico, 2012)
Specifying an eParticipation environment can be tricky, especially when selecting ICTs to support the process, since the designer must pay close attention to characteristics that, if not considered, may turn an eParticipation initiative in an ineffective one. In this paper we describe relationships from characteristics of participation methods and the so called ICT components, in order to help a designer when selecting these ICTs, thus helping him to specify eParticipation environments.